Design, Implementation, and Validation of a Praat Script to Measure Diadochokinetic Rate [Diseño, Implementación y Validación de Un Script de Praat Para Medir el Rendimiento Diadococinético] - Roman-Montes de Oca, D (STM Editores S.A, 2023)
Introduction: This research aims to implement and validate a Praat script for computing four quantitative metrics of diadochokinetic rate in digital speech samples. Notably, the script computes the average number of syllables per second, the coefficient of variability of the average number of syllables per second, average syllable length, and the coefficient of variability of average syllable length in diadochokinetic sequences. Methods: To do this, a Praat script was written and implemented to segment the syllables of diadochokinetic sequences and to calculate and deliver the four metrics above. Once the script had been implemented, and to validate the code, the results obtained for the four metrics from a sample of 30 speakers were compared with two sets of results from the same 30 speakers obtained from two different methods: (a) a single human non-automated analysis and calculation; (b) an automated analysis and calculation from a commercially available program. Results and conclusion: The validation process results did not reveal any significant differences in the performance of the three methods, which ratifies the validity of the script presented in this work. © 2022 Elsevier España, S.L.U. y Asociación Española de Logopedia, Foniatría y Audiología e Iberoamericana de Fonoaudiología